Insignificant things : amulets and the art of survival in the early Black Atlantic - Rarey, Matthew Francis (Visual arts of Africa and its diasporas., 2023)
"In Insignificant Things Matthew Francis Rarey traces the history of the African-associated amulets that enslaved and other marginalized people carried as tools of survival in the Black Atlantic world from the seventeenth to the nineteenth centuries. Often considered visually benign by white Europeans, these amulet pouches, commonly known as "mandingas," were used across Africa, Brazil, and Portugal and contained myriad objects, from herbs and Islamic prayers to shells and coins. Drawing on Arabic-language narratives from the West African Sahel, the archives of the Portuguese Inquisition, sixteenth- and seventeenth-century European travel and merchant accounts of the West African Coast, and early nineteenth-century Brazilian police records, Rarey shows how mandingas functioned as portable archives of their makers' experiences of enslavement, displacement, and diaspora. He presents them as examples of the visual culture of enslavement and critical to conceptualizing Black Atlantic art history. Ultimately, Rarey looks to the archives of transatlantic slavery, which were meant to erase Black life, for objects like the mandingas that were created to protect it"--